(untitled) (Aporte Santiaguino, 2025)
The objective of this research is to contribute and improve the physical and mechanical behavior of hot mix asphalt (HCM) by modifying the asphalt cement (AC) by adding low-density polyethylene (LDPE), this contributes to improving the quality of asphalt mixtures, supported by the parameters offered by the Marshall test. The method has a quantitative approach, cross-sectional design because the problem was analyzed in its present situation, it is experimental because it manipulates the independent variables, it is deductive since it will start from a general characterization, descriptive and explanatory. The instruments used are data collection sheets, laboratory formats. The sources used are the MTC, scientific article, thesis, books. The results obtained from the modified hot mix asphalt (MACM) with respect to the hot mix asphalt (MACC) were: density 2%, voids 15%, V.M.A -8%, Full Voids of CA -7%, Flow at 6% and Stability 16%. Finally, it is concluded that by adding LDPE, it contributes significantly to improving the quality of the MACC.